The Relationship Between Duration of Injectable Contraception Use and Increased Blood Sugar Levels: Ainun Zakiyah1, Rani Safitri2 - Ainun Zakiyah; Rani Safitr (Health and Technology Journal (HTechJ), 2026)
Long-term use of progestin-based injectable contraception, particularly depot medroxyprogesterone acetate (DMPA), may influence glucose metabolism by increasing insulin resistance, thereby elevating the risk of prediabetes and hyperglycemia. This study aims to examine the relationship between the duration of injectable contraceptive use and blood sugar levels among family planning acceptors. A quantitative correlational study with a cross-sectional design was conducted in 2025. A total of 30 respondents were selected using purposive sampling from 150 active injectable contraceptive users. Blood glucose levels were measured using a digital glucometer through random blood glucose testing, and data on the duration of injectable contraceptive use were collected via structured interviews. Data were analyzed using the Chi-Square test with a significance level of p < 0.05. Most respondents were aged 26–35 years (53.3%) and had used injectable contraception for 1–3 years (40%). Overall, 40% of participants exhibited elevated blood sugar levels, categorized as prediabetes or hyperglycemia. A statistically significant association was identified between a more prolonged duration of injectable contraceptive use and elevated blood sugar levels (p = 0.021). Prolonged use of injectable contraception is significantly associated with elevated blood sugar levels. Routine glucose monitoring and targeted health counseling are recommended for long-term injectable contraceptive users to reduce the risk of metabolic complications.